Laparoscopic re-implantation of refluxing ureter in children: A feasibility study - Haytham E. Badawy (Taylor & Francis Group, 2017)
Objective: To report our initial experience in the application of laparoscopy in the management of children with unilateral vesico-ureteric reflux (VUR) using the laparoscopic extravesical transperitoneal approach following the Lich–Gregoir technique, and to evaluate the results and benefits of this technique for such patients. Patients and methods: Between February 2013 and August 2014, 17 children [13 girls and four boys, with a median (range) age of 60 (24–120) months] presented with recurrent febrile urinary tract infections and were diagnosed with unilateral VUR. They underwent transperitoneal extravesical laparoscopic ureteric re-implantation following the Lich–Gregoir technique. Postoperatively abdomino-pelvic ultrasonography was done at 1 month after surgery and voiding cystourethrography (VCUG) at 3 months after surgery, and in cases with persistent VUR or de novo contralateral VUR another VCUG was done at 6 months after surgery. Results: The median (range) operative time was 90 (80–120) min and the postoperative hospital stay was 2 (2–5) days. Intraoperative and postoperative complications were minimal. Patients were followed-up for a median (range) of 6 (3–21) months. All the children had complete resolution symptomatically and on VCUG, without further intervention. Conclusions: The laparoscopic extravesical transperitoneal approach for ureteric re-implantation, following the Lich–Gregoir technique, is feasible and very effective in the management of VUR. Prospective randomised studies are eagerly awaited to define the benefits of this technique to patients, as well as to determine the cost-effectiveness of this approach.